Entre a História e a Literatura – Lima Barreto: narrativas sobre a pobreza nas primeiras décadas do Brasil República (1900-1922) - Silva, Marcos Renan Praciano da (2018)
The aim of this dissertation is to analyze the representation of the poor and the poverty in the writings of Lima Barreto, focusing his production in the first decades of the Brazilian republican regime (1900-1922). We also sought to understand, trought his intellectual trajectory, the ambivalent relationship he maintained towards the poor, since, although he identified himself with then in terms of color and class, he moved away in terms of intellectual formation. Methodologically based in Social History, this research was articulated o an inventory of articles, letters, short stories, chronicles, journals and novels, texts by which the author made a series of critical considerations about the relationship between the poor and the republican politics, as well as about the substance of the racial theories in force at this time. We understand that, in debating himself with this complex social place, Lima Barreto ended up bringing to light an original conception of citizenship in a time of stark social exclusion.